2019
DOI: 10.1111/jfpp.13942
|View full text |Cite
|
Sign up to set email alerts
|

Ginger essential oil and supercritical extract as natural antioxidants in tilapia fish burger

Abstract: The effects of the ginger extract obtained by supercritical CO2 extraction (SCE) and ginger essential oil (EO) on the quality changes of tilapia fish burger was investigated during refrigerated storage for 8 days. The formulations were compared with a control (without antioxidant) and one with sodium erythorbate (SE). The fish burger pH reduced from 6.7 to 6.5 after 6 days, for all formulations. Products became yellowish after 8 days. SCE and SE showed the lowest Thiobarbituric acid reactive substances (TBARS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
(45 reference statements)
1
25
0
6
Order By: Relevance
“…Lower results were found by Mattje et al. (2019) for a Tilapia burger that presented C * values of 15 and h ° of 77.1. Although the authors also worked with tilapia, they used other condiments, which caused this difference.…”
Section: Resultsmentioning
confidence: 58%
“…Lower results were found by Mattje et al. (2019) for a Tilapia burger that presented C * values of 15 and h ° of 77.1. Although the authors also worked with tilapia, they used other condiments, which caused this difference.…”
Section: Resultsmentioning
confidence: 58%
“…Almost all bioactive peptides containing Tyr, Leu, Ala, Ile, Val, Lys, Phe, Cys, Met, and His exhibit high antioxidant activities [ 9 ]. Another study also indicated that antioxidative peptides often contain hydrophobic amino acid residues, such as Pro, Tyr, Trp, Met, Gln, and Ala, which are generally considered antioxidants in some cases [ 1 , 29 , 30 ]. The present results show the following: peptide 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants are substances that counteract the oxidation reaction caused by free radicals. Antioxidants are used to extend the shelf life of foods because they reduce lipid oxidation [ 1 ]. Synthetic antioxidants are commonly used in the food industry [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Os extratos, devido a sua origem, são classificados como produtos naturais, o que tem aumentado a aceitação por parte dos consumidores, que estão cada vez mais preocupados em obter alimentos saudáveis (Sacchetti et al, 2005;Sivasothy et al, 2011;Lima Júnior et al, 2013). Antioxidantes naturais na indústria de alimentos são importantes não apenas devido a sua utilidade como método de prevenção da oxidação, aumentando a vida útil de uma grande variedade de alimentos (Ibañez et al, 2003;Fennema et al, 2010, Mesomo et al, 2012Mattje et al, 2019), mas também devido seus efeitos benéficos na saúde humana.…”
Section: Introductionunclassified